Biomass-derived carbon coated SiO2 nanotubes as superior anode for lithium-ion batteries. (5th March 2023) - Sui, Dong; Yao, Min; Si, Linqi; Yan, Kun; Shi, Jingge; Wang, Jianshe; Xu, Charles Chunbao; Zhang, Yongsheng
Abstract: Silica (SiO2 ) is regarded as a promising anode for lithium-ion batteries due to the high specific capacity, abundant resources and low cost. However, the inherently poor electrical conductivity and the huge volume variation during charge/discharge process significantly hinder the application of SiO2 . Designing nanostructured SiO2 and coating with high conductivity materials are effective methods to solve the above challenges. In this work, advanced SiO2 anodes were prepared by coating hollow SiO2 nanotubes (SNTs) with lignin or phenolated and depolymerized lignin furfural resin (PDLF)-derived carbon. The novel structure of the obtained SNTs greatly promotes the rapid transport for both Li + and electron, increases the exposed active sites for Li + insertion and accommodates the volume change of SNTs. Especially, PDLF possesses abundant functional groups, high carbon content and thermosetting property, which are beneficial to the dispersion of SNTs and formation of a cross-linked 3D conductive network. Thereby, SNTs@C-PDLF presents higher specific capacity of 661 mAh g −1  at 100 mA g −1, superior rate capability (262 mAh g −1  at 3000 mA g −1 ) and better cycling stability (549 mAh g −1  at 1000 mA g −1 after 800 cycles) compared with SNTs@C-lignin and pristine SNTs. Graphical abstract: Silica (SiO2 ) is considered to be one of the most promising anode materials due to its high theoretical specific capacity (1965 mAh g −1 ), abundant resources and low cost. However, SiO2 also faces problems such as large volume change and poor conductivity, resulting in poor rate capability and limited cycle life. In this work, we designed advanced SiO2 anodes by coating hollow SiO2 nanotubes (SNTs) with lignin-/phenolated and depolymerized lignin furfural resin (PDLF)-derived carbon. The SNTs@C-PDLF anode delivers a high discharge capacity of 911 mAh g −1 after 300 cycles. This work sheds light on the developing high-performance SiO2 anode and will promote the value added transformation and utilization of biomass. Image 1 Highlights: High-capacity SiO2 anode was prepared by coating SiO2 nanotubes with biomass-derived carbon. The hollow and porous structure of SiO2 nanotubes effectively accommodate the volume change during lithiation/delithiation. Biomass-derived porous carbon enhances the electrical conductivity and shortens Li + diffusion distance.